2020
DOI: 10.21203/rs.2.20481/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MHC associations of ankylosing spondylitis in East Asians are complex and involve non-HLA-B27 HLA contributions

Abstract: Background The association of HLA-B*27 with AS is amongst the strongest of any known association of a common variant with any human disease. Nonetheless, there is strong evidence indicating that other HLA-B alleles are involved in the disease. Large studies in European case-control cohorts have demonstrated risk associations with HLA-B*40 and multiple other HLA-B, -A and Class II alleles, and demonstrated that in that ethnic group the amino acid sequence at position 97 in HLA-B is the key determinant of HLA as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Regarding alleles other than HLA‐B*27, a previous study in 1637 east Asian AS patients 5 reported that HLA‐B*40 was associated with AS at a suggestive level (OR: 1.65, P = 2.54 × 10 −4 ) after controlling for HLA‐B*27 . HLA‐B*40 was a quite common allele in both Thai AS and the healthy, 14 and it did not show association with AS.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Regarding alleles other than HLA‐B*27, a previous study in 1637 east Asian AS patients 5 reported that HLA‐B*40 was associated with AS at a suggestive level (OR: 1.65, P = 2.54 × 10 −4 ) after controlling for HLA‐B*27 . HLA‐B*40 was a quite common allele in both Thai AS and the healthy, 14 and it did not show association with AS.…”
Section: Discussionmentioning
confidence: 97%
“…Other genes may also associate with AS. Other alleles in major histocompatibility complex (MHC) class I ( HLA‐B*40 and HLA‐C*15 ) are associated with AS, 5 and an allele in non‐MHC (ERAP 1) was reported to be associated with HLA‐B27‐positive AS in both Europeans and East Asians 5 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations